The Golden meteorite fall: Fireball trajectory, orbit, and meteorite characterization - Brown, P.G.; McCausland, P.J.A.; Hildebrand, A.R.; Hanton, L.T.J.; Eckart, L.M.; Busemann, H.; Krietsch, D.; Maden, C.; Welten, K.; Caffee, M.W.; Laubenstein, M.; Vida, D.; et al. (2023)
The Golden (British Columbia, Canada) meteorite fall occurred on October 4, 2021 at 0534 UT with the first recovered fragment (1.3 kg) landing on an occupied bed. The associated fireball was recorded by numerous cameras permitting reconstruction of its trajectory and orbit. The fireball entered the atmosphere at a 54° angle from the horizontal at a speed of 18 km s−1. The fireball reached a peak brightness of −14, having first become luminous at a height of >84 km and ending at 18 km altitude. Analysis of the infrasonic record of the bolide produced an estimated mass of (Formula presented.) kg while modeling of the fireball light curve suggests an initial mass near 70 kg. The fireball experienced a major flare near 31 km altitude where more than half its mass was lost in the form of dust and gram-sized fragments under a dynamic pressure of 3.3 MPa. The strength and fragmentation behavior of the fireball were similar to those reported for other meteorite-producing fireballs (Borovička et al., 2020). Seven days after the fireball occurred, an additional 0.9 kg fragment was recovered during the second day of dedicated searching guided by initial trajectory and dark flight calculations. Additional searching in the fall and spring of 2021–2022 located no additional fragments. The meteorite is an unbrecciated, low-shock (S2) ordinary chondrite of intermediate composition, typed as an L/LL5 with a grain density of ~3530 k gm−3, an average bulk density of 3150 kg m−3 and calculated porosity of ~10%. From noble gas measurements, the cosmic ray exposure age is 25 ± 4 Ma while gas retention ages are all >2 Ga. Short-lived radionuclides and noble gas measurements of the pre-atmospheric size overlap with estimates from infrasound and light curve modeling producing a preferred pre-atmospheric mass of 70–200 kg. The orbit of Golden has a high inclination (23.5°) and is consistent with delivery from the inner main belt. The highest probability (60%) of an origin is from the Hungaria group. We propose that Golden may originate among the background S-type asteroids found interspersed in the Hungaria region. The current collection of 18 L/LL—chondrite orbits shows a strong preference for origins in the inner main belt, suggesting multiple parent bodies may be required to explain the diversity in CRE ages and shock states.